Application of importance-satisfaction analysis and influence-relations map to evaluate design delay factors - Wang, Wei-Chih; Lin, Chia-Li; Wang, Shih-Hsu; Liu, Jang-Jeng; Lee, Ming-Tsung (Journal of Civil Engineering and Management, 2014)
Design delays can negatively influence the total completion time of a facility construction project. Knowing the factors to which design delays are most sensitive supports the time management of designs. However, factors that cause design delays are several and interrelated. This study proposes a new model to identify key factors that drive design delays. The core of the model integrates importance-satisfaction analysis (ISA) and an influence-relations map (IRM). The ISA evaluates the performance of each delay factor, while the IRM captures the causal relationships among factors. Additionally, the IRM is generated using a decision making trial and evaluation laboratory technique (DEMATEL). The model is applied to a real-world high-tech facility construction project to indicate the strengths of the model. In this investigation, four first-level delay factors and 17 second-level delay sub-factors are derived. The factor of “organization's decision making and budget constraints” is identified as the key driver of design delays in the project of interest. The results support management in determining which problem factors should be given priority attention. The proposed model can be employed in other decision-making situations that involve interrelated factors.